Eyes of an Eagle : Jean-Pierre Cenac, Patriarch: An Illustrated History of Early Houma-Terrebonne - Cenac, Christopher Everette (Book collections on Project MUSE., 2011)
In the year 1860, Jean-Pierre Cenac sailed from the sophisticated French city of Bordeaux to begin his new life in the city with the second busiest port of debarkation in the U.S. Two years before, he had descended the Pyrenees to Bordeaux from his home village of Barbazan-Debat, a terrain in direct contrast to the flatlands of Louisiana. He arrived in 1860, just when the U.S. Civil War began with the secession of the Southern states, and in New Orleans, just where there would be placed a prime military target as the war developed. Neither Creole nor Acadian, Pierre took his chances in the rura.